2018
DOI: 10.1002/jcp.26362
|View full text |Cite
|
Sign up to set email alerts
|

The STAT3/NFIL3 signaling axis‐mediated chemotherapy resistance is reversed by Raddeanin A via inducing apoptosis in choriocarcinoma cells

Abstract: Chemotherapy resistance is the major issue of choriocarcinoma. Apoptosis always is the ultimate outcome of chemotherapeutic drugs, which considered one of the reasons of resistance. We investigated the role of STAT3/NFIL3 signaling‐inhibited apoptosis in chemotherapy resistance and whether Raddeanin A (RA) could be a new drug to reverse resistance. Established three drug‐resistant cell lines as JEG‐3/MTX, JEG‐3/5‐FU, and JEG‐3/VP16. NFIL3 and STAT3 expression was evaluated in the cells. The IC50 value, apoptos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
27
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 34 publications
2
27
1
Order By: Relevance
“…Persistently active STAT3 has been identified in many human cancers and appears to be required for the continued growth or resistance to apoptosis of cultured human cancer cells. 20,25,41,42 In this study, phospho-JNK activation in- Additionally, several reports have demonstrated that there are interacting regions in STAT3 and c-Jun that participate in cooperative transcriptional activation. 14,18,19,43 These concepts support our finding that phospho-STAT3 was suppressed by the activation of phospho-JNK and phospho-c-Jun.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Persistently active STAT3 has been identified in many human cancers and appears to be required for the continued growth or resistance to apoptosis of cultured human cancer cells. 20,25,41,42 In this study, phospho-JNK activation in- Additionally, several reports have demonstrated that there are interacting regions in STAT3 and c-Jun that participate in cooperative transcriptional activation. 14,18,19,43 These concepts support our finding that phospho-STAT3 was suppressed by the activation of phospho-JNK and phospho-c-Jun.…”
Section: Discussionmentioning
confidence: 65%
“…Our research team has reported that inhibition of STAT3 phosphorylation has beneficial clinical therapeutic effects on human osteosarcoma. Persistently active STAT3 has been identified in many human cancers and appears to be required for the continued growth or resistance to apoptosis of cultured human cancer cells . In this study, phospho‐JNK activation induced significant phospho‐STAT3 degradation.…”
Section: Discussionmentioning
confidence: 67%
“…While supporting the anticancer activity of RA that has been indicated in other cancer types, [19][20][21][22][23][24][25][26][27][28] our findings unveil a tissuespecific effect of RA in prostate cancer. That is to target AR-FL and AR-Vs.…”
Section: Discussionsupporting
confidence: 84%
“…18 Preclinical studies have indicated the antitumour activity of RA against gastric cancer, colorectal cancer, breast cancer, liver cancer, choriocarcinoma, glioblastoma and osteosarcoma. [19][20][21][22][23][24][25][26][27][28] In the present study, we sought to investigate the anticancer effect of RA in prostate cancer. We found that it could suppress the activity of both AR-FL and AR-Vs to inhibit the growth of prostate cancer cells at an in vivo achievable concentration.…”
mentioning
confidence: 99%
“…However, in our study, PSTT was least sensitive to MTX among the drugs in the commonly used combination chemotherapy regimen EMA/EP. JEG-3/MTX and JEG-3R cells have been used as resistance models (27,28) to identify mechanism for chemotherapeutic resistance to MTX in choriocarcinoma (29) . JEG-3R showed more than 20-fold resistance compared to JEG-3/MTX.…”
Section: Discussionmentioning
confidence: 99%